2019
DOI: 10.1111/coa.13407
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic type I tympanoplasty is as effective as microscopic type I tympanoplasty but less invasive—A meta‐analysis

Abstract: Background Endoscopic type I tympanoplasty was originally introduced in the 1990s, and the extensive spread of this practice can be easily observed. The conventional technique performed involves the repair of a tympanic membrane perforation, and is defined as microscopic type I tympanoplasty. Objective of Review The aim of this study was the comparison of postoperative outcomes of both the endoscopic and the microscopic type I tympanoplasty. Type of Review We conducted a meta‐analysis in accordance with the Pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
26
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(48 citation statements)
references
References 29 publications
10
26
1
1
Order By: Relevance
“…With regard to the graft uptake, no significant difference was found between ET and MT. Similar results were also reported in previous meta-analytic studies of Tseng C-C et al 34 , Lee S-Y et al 35 and Pap I et al 36 . In this meta-analysis, we selected included studies that used similar operative techniques such as grafting material (temporalis fascia or perichondrium) and the graft placement method by underlay technique in order to obtain more accurate results about graft uptake rate.…”
Section: Comparable Effects Concerning Graft Uptake Rate and Hearing ...supporting
confidence: 91%
“…With regard to the graft uptake, no significant difference was found between ET and MT. Similar results were also reported in previous meta-analytic studies of Tseng C-C et al 34 , Lee S-Y et al 35 and Pap I et al 36 . In this meta-analysis, we selected included studies that used similar operative techniques such as grafting material (temporalis fascia or perichondrium) and the graft placement method by underlay technique in order to obtain more accurate results about graft uptake rate.…”
Section: Comparable Effects Concerning Graft Uptake Rate and Hearing ...supporting
confidence: 91%
“…The reported graft success rates of tympanoplasty vary between studies, but a meta-analysis by Pap, et al 16) showed that the graft uptake rate of endoscopic tympanoplasty was 86.9% (159/183) in randomized controlled trials and that the overall average success rate was 90.5% (503/556). A microscopic tympanoplasty success rate of 89.0% (163/183) was achieved in randomized controlled trials, and of 88.3% (550/623) in overall cases.…”
Section: Discussionmentioning
confidence: 99%
“…7,8 Various studies have been done comparing the conventional microscopic postauricular approach and endoscopic transcanal approach for TM repair with comparable outcomes with regard to graft success and hearing gain and the endoscopic method having additional advantages of anterior margin visibility, minimal invasiveness, lesser operative time, lesser postoperative pain and better cosmesis. [9][10][11][12][13][14] Regarding the size, large and subtotal perforations have lesser rates of success of graft uptake whereas in terms of the site, anterior and marginal perforations have been reported for having a negative impact over the success of type-1 tympanoplasty. [15][16][17] There are numerous studies highlighting the problematic anterior quadrant perforation repair for which several modified techniques and methods have been incorporated like the Gerlach quilt method, anterior hitch method, Kerr flap technique, 360degree subannular tympanoplasty, anterior interlay myringoplasty, window shade technique, circumferential flap method and anterior tucking technique.…”
Section: Introductionmentioning
confidence: 99%